IMPLEMENTASI KEBIJAKAN PERATURAN GUBERNUR LAMPUNG DALAM UPAYA PENEGAKAN SADAR TERTIB ARSIP DI PEMERINTAHAN PROVINSI LAMPUNG - Diding Bajuri; Sahara Taloren (e-JKPP, 2023)
The purpose of this research topic is to find out how the Lampung Provincial Government's efforts in building awareness of orderly archives through the implementation of the Lampung Governor Regulation, what are the obstacles faced by the Lampung Provincial Government in its efforts to enforce orderly archives through the implementation of the Lampung Governor Regulation, and how efforts are made by the Lampung Provincial Library and Archives Office, especially the Archival Development and Supervision Division, in overcoming existing obstacles. The method used in this research is the descriptive analysis method. Data was obtained directly from informants using interview and observation techniques. The results showed that the implementation of the Lampung Governor Regulation on Guidelines for Maintenance of Dynamic Archives and Archival Supervision has been carried out but is not yet optimal. Based on the results of the study, it indicates that communication related to information received by archive managers has not been well received. This is evidenced by the lack of maximum implementation of dynamic archive maintenance in the regional apparatus and the lack of facilities and infrastructure needed to maintain dynamic archives, both active and inactive.